Odpowiedzi

Najlepsza Odpowiedź!
2010-01-16T19:47:14+01:00
A)
2x - 3y = 7|*5
3x - 5y = 11|*(-3)

10x-15y=35
-9x+15y=-33
x=2
2*2-3y=7

x=2
-3y=7-4|:(-3)

x=2
y=-1


b)
5p - 2r = 21|*5
3p + 5r = -6|*2

25p-10r=105
6p+10r=-12
31p=93|:31
p=3

p=3
5*3-2r=21

p=3
-2r=21-15|:(-2)

p=3
r=-3


c)
2x - 3y = 10|*5
5x + 5y = 0|*3

10x-15y=50
15x+15y=0
25x=50|:25
x=2

x=2
2*2-3y=10

x=2
-3y=10-4|:(-3)

x=2
y=-2


d)
3x + y = 5
2x - y = 0
5x=5|:5
x=1

x=1
3*1+y=5

x=1
y=5-3

x=1
y=2


e)
2x - y = 5
x + y = 4
3x=9|:3
x=3

x=3
2*3-y=5

x=3
-y=5-6|:(-1)

x=3
y=1


f)
- x - y = -6
- x + y = 2
-2x=-4|:(-2)
x=2

x=2
-2-y=-6

x=2
-y=-6+2|:(-1)

x=2
y=4
1 5 1